Simultaneously Optimize the Response Speed and Sensitivity of Low Dimension Conductive Polymers for Epidermal Temperature Sensing Applications - Zhou, Cheng; Tang, Ning; Zhang, Xiaoshuang; Fang, Ye; Jiang, Yang; Zhang, Hainan; Duan, Xuexin (Frontiers in Chemistry, 2020)
Low dimension poly(3,4-ethylenedioxythiophene) poly (styrenesulfonate) (PEDOT: PSS) has been applied as resistor-type devices for temperature sensing applications. However, their response speed and thermal sensitivity is still not good enough for practical application. In this work, we proposed a new strategy to improve the thermal sensing performance of PEDOT: PSS by combined micro/nano confinement and materials doping. The dimension effect is carefully studied by fabricating different sized micro/nanowires through a low-cost printing approach. It was found that response speed can be regulated by adjusting the surface/volume (S/V) ratio of PEDOT: PSS. The fastest response (<3.5 s) was achieved by using nanowires with a maximum S/V ratio. Besides, by doping PEDOT: PSS nanowires with Graphene oxide (GO), its thermo-sensitivity can be maximized at specific doping ratio. The optimized nanowires-based temperature sensor was further integrated as a flexible epidermal electronic system (FEES) by connecting with wireless communication components. Benefited by its flexibility, fast and sensitive response, the FEES was demonstrated as a facile tool for different mobile healthcare applications.